11.8k views
0 votes
Given f(x) =3x-1 and g(x)=2x-3, for which value of x does g(x) =f(2)?

User Danish Ali
by
6.1k points

2 Answers

3 votes

Answer:

g(x) = f(2)

2x - 3 = 3*2 - 1

2x - 3 = 5

2x = 8

x = 4

User TwistedBlizzard
by
5.9k points
3 votes

For this case, we want to know what value of "x" makes:


g (x) = f (2)

To find f (2), we substitute
x = 2in f (x).


f (x) = 3x-1\\f (2) = 3 (2) -1\\f (2) = 6-1\\f (2) = 5

Now:


g (x) = f (2)\\g (x) = 5\\2x-3 = 5

Adding 3 to both sides:


2x = 5 + 3\\2x = 8

Dividing between 2 on both sides:


x = \frac {8} {2}\\x = 4\\Thus,\ x = 4\ makes\ g (x) = f (2)

Answer:


x = 4


User AlwaysVBNET
by
6.2k points